MEMO_MOVE: Effect of combined exercise and cognitive stimulation on fitness and cognitive function of individuals with mild cognitive impairment - Rondão, Catarina Alexandra de Melo (2024)
After the sixth decade of life, the incidence and prevalence of dementia diseases doubles every five years. Portugal is an aging nation, therefore presents a high prevalence of Dementia or mild cognitive impairment (MCI). Dementia is a condition in which there is progressive deterioration in cognition that affects day to day function and englobes numerous neuropathological conditions, such as Alzheimer disease, vascular dementia, multi-infarct dementia, Lewy body dementia or Parkinson's disease dementia. Physiologically, dementia is related with aberrant accumulation of damaged macromolecule caused by age-related oxidative stress increase, that can result in silent chronic inflammatory processes, reducing neurotrophines action and impairing the maintenance of cognitive performance. In this scenario, physical activity seems to help the reduction of chronic inflammation in the central nervous system, increasing neuroplasticity and promoting remodulation of neuronal circuits by increasing cerebral blood flow. MCI is a syndrome defined as cognitive decline greater than expected for an individual's age and education level but that does not interfere notably with activities of daily life and often is a precursor of Dementia. Regular exercise has emerged as one of the most crucial lifestyle factors for improving both physical and cognitive performance among the elderly. However, although there are some indications of the benefits of aerobic exercise in reducing oxidative stress, little is known about (1) the evidence of the benefits of exercise on dementia; (2) the most adequate exercise plan to promote benefits on physical and cognitive function and (3) the benefits of multicomponent exercise (combination of exercise and cognitive stimulation) on physical fitness and cognitive function among people with Dementia or MCI. To address these questions several works were carried out: (1) a critical review based on revision articles concerned the evidenced effects of physical exercise in people with MCI were made. Main conclusions enhance the benefits that patients with dementia have from various exercise programs to improve global cognition, especially in the early to moderate stage of the disease. (2) In order to be more successful in the intervention, it was important to find out among the professionals working with these subjects which aspects they consider most relevant in the planning, and which are the main constraints. The main aspects mentioned were related with recommendations, such as the importance of including families and caregivers; the need to educate families and caregivers about the importance of physical exercise in dementia; respect the patient's will to participate; promote the collaboration and involvement of the senior residence staff; ensure attentive, respectful, and friendly treatment; create a relationship of trust with the exercise professional; the appropriate design of physical exercise and cognitive stimulation; an appropriate schedule; and a safe environment. Additionally, the main concerns were related to dementia patients' resistance to participate in exercise programs, inappropriate activities or exercises; the risk of falls; the lack of exercises’ adaptation; the difficulty in understanding instructions; the physical space for the implementation of programs not always being the most adequate; the lack of family support; the inadequate diagnosis of dementia; the danger of disorientation; episodes of violence; the willingness of people involved in the care of demented patients to collaborate; the lack of sensitivity in the treatment of people with MCI/Dementia; and the lack of adequate exercise equipment in nursing homes. (3) The physical fitness level in older persons with mild cognitive impairment was assessed, evidencing that is very poor among this population, with severe consequences on their functional independence. Therefore, promoting an active lifestyle among this population should be a crucial concern, to maintain motor abilities to perform daily tasks. (4) In order to establish the intervention characteristics, a literature review was conducted to collte and analyze previous work, which provided a summary the type of exercise that should be implemented among this population. The MEMO_MOVE program was structured and described, regarding (i) inclusion of a cognitive stimulation component; (ii) the kind of cognitive stimulation; and (iii) the type of exercise, duration, frequency, intensity, and program length. (5) After the identification of the key aspects to include in the exercise program for subjects with MCI, and paying attention to the main recommendations and constrains identified by the professionals that take care of these people, a study to evaluate the effects of a multicomponent exercise program on cognitive function and physical fitness in elderly people with mild cognitive impairment and to identify the role of oxidative stress and brain derived neurotrophic factor (BDNF), had been carried out. At baseline, 37 elderly nursing home residents with mild cognitive impairment were divided into two groups: the control group (CG, n = 12, 81.8 years) and the experimental group (EG, n = 25, 83.2 years). These elderlies followed multicomponent exercise training with dual task for 24 weeks, with two sessions per week and 45–50 min per session. Exercises included strength training and aerobic exercises, taking into consideration functional movement and light to moderate intensity. Cognitive stimulation included computer exercises, balanced platform games, word games, puzzles, math calculations, progressive and regressive counting, and word games. Physical assessments (weight, height, and body mass index), health and functional parameters (fitness tests: chair stand, arm curls, chair sit-and-reach, eight feet up-and-go, back scratch, 6-min walking, feet together, semi-tandem, and full tandem), lipid profile (total cholesterol, high-density lipoprotein (HDL), low-density lipoprotein (LDL), and triglycerides), measures of lipid peroxidation damage, thiobarbituric acid reactive substances (TBARS), total antioxidant capacity (TAC), and BDNF were measured in plasma, based on which analyses were performed before and after the 24 weeks of the multicomponent exercise intervention. The main results showed an overall improvement in physical and functional performance. Regarding cognitive function, there were significant improvements in the cognitive performance, particularly in retention and recall capacity. Significant different variations between groups in Total Cholesterol between baseline and post intervention period, occurred. The plasma biochemical parameters of BDNF, decrease in both groups between baseline and post intervention. Total antioxidant capacity increased in both groups, however while CG increased lipid peroxidation, EG decreased it. The results suggest that a multicomponent exercise training program (aerobic and strength exercises combined with cognitive stimulation) in institutionalized elderly with MCI is effective in improving physical fitness, memory and reducing oxidative stress-induced damage.